Implementation of Quizizz-Based Microlearning on Basic Physics Cognitive Learning Outcomes - Tutik Yuliatun (Pendidikan IPA, FMIPA, UNP, 2023)
This study attempts to show how quizizz-based microlearning has affected the cognitive learning outcomes for basic physics. 39 students participated in the activity that was the focus of this study. A pretest-posttest design with one group was the research methodology used in this study. Methods for gathering data that involve tests. The normality test and paired sample T-test were applied during the data analysis process. The paired sample t-test yielded data of 0.00, indicating that the use of Quizizz-based microlearning had an impact on the cognitive learning outcomes for basic physics.